Study of low density parity-check LDPC codes - BENAISSA Mourad; TEBIB Billal; Challali Safouane (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2022)
LDPC codes are currently one of the hottest topics in coding theory they were invented in the early 1960s and have made an incredible comeback in recent years. LDPC codes, unlike many other types of codes, already have very fast encoding and decoding algorithms. The question is how to design the codes so that these algorithms can recover the original code word even in the presence of lot of noise. The design problem can now be solved using new analytic and combinatorial tools. As a result, LDPC codes are not only appealing from a theoretical standpoint, but also ideal for practical applications. In this study, we will provide a brief history of LDPC codes as well as the methods used to analyze and design them.
OPTION : Telecommunication System